2021
DOI: 10.31575/jp.v5i1.337
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Budaya Organisasi, Komitmen Organisasi Dan Stres Kerja Terhadap Turnover Intention Karyawan PT. Brahma Bina Bakti Mill Jambi

Abstract: Fast traslate Icon translate     Fast traslate Icon translate Turnover intention is the intention of leaving an employee from a company and looking for alternatives to other companies or other jobs. Turnover intention is generated on the basis of the workload experienced by employees. This study aims to determine the relationship between organizational culture, organizational commitment and work stress and turnover intention on employees. The population of this study were employees who worked in the PT. Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Employees who lack a sense of ownership over their work, causing it not to be completed on time, are one example of the decline in organizational commitment felt by PT Sarana Global Telecom employees, as are employees who are not disciplined when coming to work. https://publikasi.mercubuana.ac.id/index.php/indikator Earlier research also supports the results of this study, as shown by Rahmizal & Lasmi (2021), Lubis & Onsardi (2021), Ekhsan (2019), Pramudika et al (2017), andPratama et al (2022) show that turnover intention is significantly and negatively influenced by organizational commitment. The findings of this study match the reality of PT Sarana Global Telecom.…”
Section: ) the Influence Of Organizational Commitment On Turnover Int...supporting
confidence: 86%
See 2 more Smart Citations
“…Employees who lack a sense of ownership over their work, causing it not to be completed on time, are one example of the decline in organizational commitment felt by PT Sarana Global Telecom employees, as are employees who are not disciplined when coming to work. https://publikasi.mercubuana.ac.id/index.php/indikator Earlier research also supports the results of this study, as shown by Rahmizal & Lasmi (2021), Lubis & Onsardi (2021), Ekhsan (2019), Pramudika et al (2017), andPratama et al (2022) show that turnover intention is significantly and negatively influenced by organizational commitment. The findings of this study match the reality of PT Sarana Global Telecom.…”
Section: ) the Influence Of Organizational Commitment On Turnover Int...supporting
confidence: 86%
“…The desire of a worker to stay with the firm and actively engage in it is referred to as organizational commitment. The results of previous research conducted by Rahmizal and Lasmi (2021), Lubis and Onsardi (2021), Ekhsan (2019), Pramudika et al (2017), andPratama et al (2022) demonstrate that the motivation for quitting a company is significantly Career development, according to Busro (2018), is the process of an employee having a business or activity with an expected aim, such as employment, that is in line with his or her competence and career. Career development is one of the things an employee can do to help them achieve their goals as an employee.…”
Section: Relationship Between Organizational Commitment and Turnover ...mentioning
confidence: 94%
See 1 more Smart Citation
“…An organizational culture that provides recognition and appreciation to employees and provides opportunities to provide feedback and suggestions to management can reduce turnover intention. Apart from that, other research by Rahmizal & Novia (2021) revealed that organizational culture has a negative and significant effect on turnover intention. The greater the organizational culture of a company, the lower the level of turnover intention.…”
Section: )mentioning
confidence: 88%